2019
DOI: 10.1007/s00127-019-01742-6
|View full text |Cite
|
Sign up to set email alerts
|

Untethered lives: barriers to societal integration as predictors of the sexual orientation disparity in suicidality

Abstract: Purpose Despite increasing legal protections and supportive attitudes toward sexual minorities (e.g., those who identify as lesbian, gay, and bisexual [LGB]) in recent decades, suicidality remains more common among this population than among heterosexuals. While barriers to societal integration-or a lack of meaning, purpose, and belonging as derived from societal norms, goals, and attachment-have been widely theorized as determinants of suicidality for the general population, they have not been comprehensively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…31−33 Additional potential mechanisms and risk factors that have been linked to suicide risk among LGB individuals include higher rates of social isolation (e.g., living alone, never having been married), financial insecurity, and substance use. 34,35 Moreover, lesbian/bisexual women are more likely to be gun owners than heterosexual women, 36 and gun accessibility increases suicide risk. 37 Black and Hispanic heterosexual men and women had a significantly lower risk of suicide outcomes than White heterosexual peers; yet, similar trends were not observed among LGB adults.…”
Section: Discussionmentioning
confidence: 99%
“…31−33 Additional potential mechanisms and risk factors that have been linked to suicide risk among LGB individuals include higher rates of social isolation (e.g., living alone, never having been married), financial insecurity, and substance use. 34,35 Moreover, lesbian/bisexual women are more likely to be gun owners than heterosexual women, 36 and gun accessibility increases suicide risk. 37 Black and Hispanic heterosexual men and women had a significantly lower risk of suicide outcomes than White heterosexual peers; yet, similar trends were not observed among LGB adults.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Krueger, Meyer, & Upchurch (2018) found higher perceived stress mediated the association between a sexual minority identity and depression in an adult sample from the United States. Similar for suicide-related outcomes, Bränström et al (2020) identified various psychological factors (e.g., depression), interpersonal risk factors (e.g., discrimination), and barriers to societal integration (e.g., being unemployed) as mediators. Yet, despite evidence supporting heightened stress is pervasive across various areas of life among sexual minority populations (e.g., stress related to one's financial situation, health, love life, family relations, health of family members; Frost et al, 2015;Hatzenbuehler, 2011;McGarrity, 2014;Rostosky et al, 2007), little research has tested perceived life stress as a predictor of suicide-related outcomes and NSSI behaviors or how these associations may differ among specific sexual orientation groups (i.e., heterosexual students reporting SGA, asexual, and unsure).…”
Section: Introductionmentioning
confidence: 93%
“…Social isolation represents a final plausible mediator of the association between structural stigma and poor mental health. Sexual minorities experience more social isolation than heterosexuals across the life span; in turn, social isolation is associated with poor mental health outcomes among sexual minorities (e.g., Bränström et al, 2020). Although stigma in the form of interpersonal discrimination is particularly likely to result in social isolation among sexual minorities, even more so than among racial/ethnic minorities (Hatzenbuehler et al, 2009), we are aware of only one study that has examined whether structural stigma might represent another source of social isolation among sexual minorities (Perales & Todd, 2018).…”
Section: General Scientific Summarymentioning
confidence: 99%